MOTIVASI MEMEDIASI PENGARUH KOMITMEN PROFESIONAL TERHADAP KEPUASAN KERJA PERAWAT RSUD KABUPATEN KLUNGKUNG - Sumandari, Nyoman Yustiana; Wibawa, I Made Artha (E-Jurnal Manajemen, 2021)
A person's job satisfaction is influenced by several aspects, such as having the motivation and professional commitment needed to encourage a professional to do his job and develop the abilities he has in doing his job. This research is conducted at the Klungkung District General Hospital with 120 civil servant nurses as a sample using nonprobability sampling method. Data were collected using a questionnaire and analyzed by path analysis. The results show that Professional Commitment has a positive and significant effect on Job Satisfaction; Work Motivation has a positive and significant effect on Job Satisfaction; Professional Commitment has a positive and significant effect on Work Motivation; and Professional Commitment has a positive and significant effect on Nurse Job Satisfaction mediated by Work Motivation. Keywords: Professional Commitment, Motivation, Job Satisfaction